Involvement of bactericidal factors from thrombin-stimulated platelets in clearance of adherent viridans streptococci in experimental infective endocarditis. - Dankert, J (1995)
Platelets activated with thrombin release bactericidal factors. We studied the role of the susceptibility of viridans streptococci to these bactericidal factors in the development of infective endocarditis (IE). By using the experimental endocarditis rabbit model, the initial adherence and the development of IE were assessed for 10 viridans streptococcal strains differing in their susceptibilities to releasate (material released) from thrombin-activated platelets. Six strains were susceptible and four strains were resistant to these releasates. The numbers of vegetations (VGs) colonized at 5 min and 48 h after intravenous challenge with 10(4) CFU were determined. At 5 min after challenge, significantly more VGs were colonized with bacteria of the six platelet releasate-susceptible strains than with bacteria of the four releasate-resistant strains (P < 0.005). In the releasate-susceptible group of strains, the number of colonized VGs decreased significantly between 5 min and 48 h after intravenous inoculation (P < 0.001). Such a decrease was not observed with the releasate-resistant strains. As a result, the final developments of IE due to releasate-susceptible and -resistant strains were not significantly different. The releasate-susceptible strain 1 and the releasate-resistant strain 2 were selected for more detailed experiments. Rabbits were killed at 5 and 30 min and 2, 4, and 48 h after inoculation. The number of culture-positive VGs as well as the number of adherent bacteria on the individual VGs were determined. The 90% infective dose for each strain was 10(5) CFU. At low inoculum concentrations (10(3) and 10(4) CFU) a larger proportion of the inoculated bacteria of both strains was found to be adherent on VGs than at higher challenge doses. The number of culture-positive VGs as well as the number of adherent bacteria per VG decreased rapidly in the first 30 min after challenge with strain 1 but not after challenge with strain 2. Additional experiments with the platelet releasate-susceptible strain S224 and the platelet releasate-resistant stain S182 confirmed the data obtained with strains 1 and 2 and indicated that releasate-susceptible strains disappeared from the VGs with time, whereas releasate-susceptible strains persisted. In vitro studies with VGs excised 5 min after challenge with stain 1 or 2 showed that clearance of the releasate-susceptible strain 1 was not caused by complement bactericidal activity or surface phagocytosis by polymorphonuclear cells. Bacterial cells of strain 1 adherent on excised VTGs were rapidly cleared by exposure to fresh clotting blood or to releasates from thrombin-stimulated platelet suspension.(ABSTRACT TRUNCATED AT 400 WORDS)